Re-imagining personhood: dementia, culture and citizenship. Issue 2 (3rd April 2021) - Swinton, John
ABSTRACT: The paper explores the issue of personhood and citizenship. It looks at some of the philosophical and cultural challenges that accompany the experience of dementia and offers a way of thinking that can hold together the vital relationality that comes with certain models of philosophical personhood with the more concrete and politically engaged understandings of dementia that come through a focus on citizenship in general and social citizenship in particular. It suggests that if we bring together relational models of personhood with citizenship approaches, we can end up with a politically informed spirituality that has much potential in terms of developing and protecting the well-being of people living with dementia and those who seek to offer care and support.